PENGARUH KOMPENSASI DAN PENGEMBANGAN KARIR TERHADAPKEPUASAN KERJA PERAWAT YANG DIMEDIASI OLEH MOTIVASI KERJA PADA RUMAH SAKIT BINA KASIH PEKANBARU - Gunawan, Andri; Fitri, Kurniawaty; ', Machasin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
Bina Kasih Hospital is an organization / institution that is engaged in providing services and and has the intent and purpose to promote and improve health services in Pekanbaru. In carrying out its activities, the service is something that must be considered by the management of the hospital because the hospital is an activity engaged in services. Therefore, satisfactory service would be a good image for the hospital so that it can be a reference for prospective patients to seek treatment at the hospital. In the enterprise, human factors on the employees themselves will evolve into complex problems, such as poor work performance, low work ethic, high employee turnover and other things that can inhibit the development and achievement of corporate goals.The purpose of this study is to look at the effect of compensation and career development to job satisfaction of nurses that is mediated by the motivation to work at Bina Kasih Hospital Pekanbaru. The population in this study were all employees of Bina Kasih Hospital Pekanbaru totaling 72 people with census sampling method. This study using path analysis (path) with SPSS 21.Results of the study found that compensation and career development is significant and positive impact on the motivation of the nurses at Bina Kasih Hospital Pekanbaru. While the motivation, compensation and career development is significant and positive impact on job satisfaction of nurses at Bina Kasih Hospital Pekanbaru. Then motivation does not mediate the effect of compensation and career development to job satisfaction of nurses at Bina Kasih Hospital.Keywords : Compensation, Career Development, Motivation and Job Satisfaction